2022
DOI: 10.1021/acsomega.1c05090
|View full text |Cite
|
Sign up to set email alerts
|

Pulicaria undulata Extract-Mediated Eco-Friendly Preparation of TiO2 Nanoparticles for Photocatalytic Degradation of Methylene Blue and Methyl Orange

Abstract: Eco-friendly approaches for the preparation of nanomaterials have recently attracted considerable attention of scientific community due to rising environmental distresses. The aim of the current study is to prepare titanium dioxide (TiO 2 ) nanoparticles (NPs) using an eco-friendly approach and investigate their performance for the photocatalytic degradation of hazardous organic dyes. For this, TiO 2 NPs were prepared by using the aqueous extract of the Pulicaria undulata (L.) plant in a single step at room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…As a result, the −NH 2 group molecule produced during the reduction reaction of MO dye was ascribed to the new peak appearance at 252 nm with an increase in intensity. 47 It has been already reported that AgNPs minimize MO dye at the azo linkage in the presence of sodium borohydride and provoke free amino group hydrazine derivative, low molecular compounds, 48,49 as demonstrated in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the −NH 2 group molecule produced during the reduction reaction of MO dye was ascribed to the new peak appearance at 252 nm with an increase in intensity. 47 It has been already reported that AgNPs minimize MO dye at the azo linkage in the presence of sodium borohydride and provoke free amino group hydrazine derivative, low molecular compounds, 48,49 as demonstrated in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Al-hamoud et al (2022) reported phytomolecule functional groups present (3425, 2917, 2849, 1630, 1070, and 625 cm –1 , respectively) in the Pulicaria undulata plant extract. 24 The FT-IR spectrum of TDO NPs3 at 300 °C is shown in Figure 3 B, with the absorption band at 3321.25 cm –1 corresponding to the stretching vibration of the −OH group, the peak at 1639.13 cm –1 corresponding to the stretching vibration of alkene (−C=C−), and the band at 423.25 cm –1 corresponding to the stretching vibration of titanium metal and oxygen (Ti–O) bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The flexural vibration of aliphatic carbon and hydrogen is responsible for the peak at 720.44 cm −1 (−C−H). Al-hamoud et al (2022) reported phytomolecule functional groups present (3425, 2917, 2849, 1630, 1070, and 625 cm −1 , respectively) in the Pulicaria undulata plant extract 24. The FT-IR spectrum of TDO NPs3 at 300 °C is shown in Figure3B, with the absorption band at 3321.25 cm −1 corresponding to the stretching vibration of the −OH group, the peak at 1639.13 cm −1 corresponding to the stretching vibration of alkene (−C� C−), and the band at 423.25 cm −1 corresponding to the stretching vibration of titanium metal and oxygen (Ti−O) bonds.Our current findings are consistent with those of FT-IR bands (34246, 3430, 1642, 1529, 1450, 1134, 1168, 1092, and 469 cm −1 ) of TiO 2 -supported biochar reported by Abodif et al…”
mentioning
confidence: 99%
“…Pulicaria undulata extract-mediated eco-friendly synthesis of TiO 2 has been reported by Khaleel Al-hamoud et al (Al-hamoud et al, 2022). They were tested for the degradation of MB and MO under UV-vis light irradiation.…”
Section: Some Case Studies Of Photocatalytic Activity Of Green Synthe...mentioning
confidence: 99%